Efficiency improvement of rooftop photovoltaic system at railway station. Issue 1 (1st January 2017) - Igarashi, Takeshi; Kumano, Teruhisa; Hayashiya, Hitoshi; Takino, Toshiaki
Abstract: The partial shadows on the photovoltaic (PV) system are widely recognized to slightly influence the amount of generation power. The power output drop does not clearly break out according to the actual area covered by the shadows. The influence of partial shadows on the PV system installed on the rooftop of Tokyo Station is evaluated in this paper. Changing the circuit configuration in the PV string is effective in minimizing the decrease of the power output in the PV system with partial shadows.